Evolusi Doktrin Pertahanan Indonesia sebagai Negara Maritim - Hardianto, Muhammad Khusna Bayu (Universitas Muhammadiyah Sorong, 2021)
Indonesia's foreign policy in the era of President Joko Widodo's administration focused on national maritime awareness. With its strategic geographic and geopolitical potential, it is realized that there are also potential threats. By using qualitative research method and the concept of Revolution on Military Affairs, this article discusses the increase and adjustment of national maritime defense posture, and also the changes in military doctrine that followed by strategic policies supporting the Revolution on Military Affairs in Indonesia as a maritime country.